2015
DOI: 10.1155/2015/930874
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder and Amplified Pain

Abstract: Among the core features of ASD, altered sensitivities in all modalities have been accorded increasing importance. Heightened sensitivity to pain and unusual expressions of and reaction to pain have not hitherto been widely recognised as a presenting feature of ASD in general paediatrics. Failure to recognise ASD as a common cause of pain can lead to late diagnosis, inappropriate treatment, distress, and further disability. Two cases are presented which illustrate the late presentation of Autism Spectrum Disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 17 publications
6
41
0
Order By: Relevance
“…Opposing direction of effect of genetic variants on MCP versus low RA may mean that insomnia and other sleep difficulties (for which low RA represents a proxy phenotype) associated with MCP are due to environmental and lifestyle factors related to chronic pain, rather than shared genetic factors predisposing to increased risk for both traits. There was also significant negative genetic correlation between MCP and both AN and ASD, which may be linked to changes in interoception and atypical pain experience seen in individuals with these conditions (Strigo et al, 2013;Bär et al, 2015;Clarke, 2015;Bischoff-Grethe et al, 2018;Gu et al, 2018), and may suggest a genetic basis for increased pain thresholds.…”
Section: Genetic Correlationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Opposing direction of effect of genetic variants on MCP versus low RA may mean that insomnia and other sleep difficulties (for which low RA represents a proxy phenotype) associated with MCP are due to environmental and lifestyle factors related to chronic pain, rather than shared genetic factors predisposing to increased risk for both traits. There was also significant negative genetic correlation between MCP and both AN and ASD, which may be linked to changes in interoception and atypical pain experience seen in individuals with these conditions (Strigo et al, 2013;Bär et al, 2015;Clarke, 2015;Bischoff-Grethe et al, 2018;Gu et al, 2018), and may suggest a genetic basis for increased pain thresholds.…”
Section: Genetic Correlationsmentioning
confidence: 94%
“…This has been observed for Major Depressive Disorder (MDD) (Nicholl et al, 2014;McIntosh et al, 2016), post-traumatic stress-disorder (PTSD) (Shipherd et al, 2007;Dunn et al, 2011;Phifer et al, 2011;Outcalt et al, 2015;Akhtar et al, 2018), schizophrenia (Watson, Chandarana and Merskey, 1981;de Almeida et al, 2013;Engels et al, 2014) and bipolar disorder (BD) (Nicholl et al, 2014;Stubbs et al, 2015). There are also reported differences in the perception of pain and interoception (sensing and integration of bodily signals) for people with schizophrenia (Lévesque et al, 2012;Urban-Kowalczyk, Pigońska and Śmigielski, 2015), anorexia nervosa (AN) (Strigo et al, 2013;Bär et al, 2015;Bischoff-Grethe et al, 2018) and autism spectrum disorders (ASD) (Clarke, 2015;Gu et al, 2018), with some evidence of an increase in pain thresholds for AN and ASD.…”
Section: Genetic Correlationsmentioning
confidence: 95%
“…Also, another aspect worth mentioning here is represented by the pain perception in autistic pathology, which is known to be quite a problem, especially considering that now the classical theories stating that most of the ASD patients have lowered or even abolished sensitivity to pain [20,21], are questioned and challenged heavily to this date [22][23][24], since oxytocin was previously cited as having some interesting analgesic effects [25,26].…”
mentioning
confidence: 99%
“…Hypo-and hyper-sensitivity to sensory are presented in individuals with autism [Hashimoto, Tayama, & Miyao, 1986]. Of the sensory abnormalities that were recognized for autism is either heightened or reduced sensitivity to pain [Clarke, 2015]. Recently, a neuroimaging study of high-functioning adults with ASD showed heightened brain response to pain anticipation, which is related to social impairments in individuals with autism [Gu et al, 2018].…”
Section: Discussionmentioning
confidence: 99%